2013
DOI: 10.3389/fpsyt.2013.00058
|View full text |Cite
|
Sign up to set email alerts
|

How Much Child Sexual Abuse is “Below the Surface,” and Can We Help Adults Identify it Early?

Abstract: Child sexual abuse (CSA) occurs frequently in society to children aged between 2 and 17. It is significantly more common in girls than boys, with the peak age for CSA occurring when girls are aged 13–17. Many children experience multiple episodes of CSA, as well as having high rates of other victimizations (such as physical assaults). One of the problems for current research in CSA is different definitions of what this means, and no recent review has clearly differentiated more severe forms of CSA, and how com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
1
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(50 citation statements)
references
References 72 publications
2
40
1
2
Order By: Relevance
“…In the age-group of 2–17 years, nearly 15% of girls and 6% of boys face severe consequences of CSA. [6]…”
Section: Global Scenario Of the Problemmentioning
confidence: 99%
See 2 more Smart Citations
“…In the age-group of 2–17 years, nearly 15% of girls and 6% of boys face severe consequences of CSA. [6]…”
Section: Global Scenario Of the Problemmentioning
confidence: 99%
“…[346912] The overall prevalence is seen to be high among both gendersthough studies suggest girls are more prone than boys[346910111219203132], few studies report that there is no difference[16], while some others report males to be more prone. [18] In most (95%) of the cases, the perpetrator is known to the child (relatives, neighbors, step parents, highly trusted people).…”
Section: Who Are More Vulnerable To Csa?mentioning
confidence: 99%
See 1 more Smart Citation
“…The use of legally defined cases are likelyto underestimate the true prevalence of childhood maltreatment (Theodore et al, 2005) and may account for the observed weak associations, particularly for sexual abuse (Martin and Silverstone, 2013). Maltreated children may have substantially higher rates of early alcohol and tobacco use (Mills et al, 2014), possibly gateways to subsequent cannabis use (Fergusson et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to prior studies (Hayatbakhsh et al, 2009), however, sexual abuse was not significantly associated with cannabis use disorders. For instance, it is possible that sexual abuse is underreported (Martin and Silverstone, 2013) because of inconsistent definitions (Martin and Silverstone, 2013), secrecy (Polonko, 2006) and stigma . Conversely, the nature and severity of sexual abuse (Hahm et al, 2010;Kendall-Tackett and Becker-Blease, 2004), may mean that it is more likely to be reported and attract an agency response before there is progression to long-term disorders (Kendall-Tackett and Becker-Blease, 2004) involving cannabis use.…”
Section: Discussionmentioning
confidence: 99%